2019
DOI: 10.3390/microorganisms7090331
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Anti-Inflammatory Lingonberry Mouthwash—A Clinical Pilot Study in the Oral Cavity

Abstract: Fermented lingonberry juice was designed to be used as a mouthwash. Our aim was to study the antimicrobial and anti-inflammatory effects of the mouthwash in the oral cavity. A clinical study of 30 adult participants was performed. A total of 20 participants used 10 mL of the mouthwash twice daily for two weeks and 10 participants used 20 mL twice daily for one week. Streptococcus mutans, Candida and Lactobacilli were cultivated at the beginning, after the mouthwash period and after a washout period. At the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…Lingonberry polyphenols have also been proposed to act as antivirals [39], and in this regard, lingonberries have been shown to possess in vitro antiviral activity [40]. Other studies have also reported lingonberry's antibacterial and antifungal activities: inhibition of growth of Candida, S. mutans, Porphyromonas gingivalis, Fusobacterium nucleatum, S. aureus, Salmonella enterica sv Typhimurium, S. epidermidis, P. gingivalis, P. intermedia, antiaggregation of S. mutans with Fusobacterium nucleatum or Actinomyces naeslundii, anti-adhesiveness of Neisseria meningitidis or oral streptococci in biofilm formation, and binding activity of Streptococcus pneumoniae, Streptococcus agalactiae and Streptococcus suis to berries and juices [36,[41][42][43][44][45][46][47][48][49][50][51][52]. No effects of lingonberries on lactobacilli have been found in any of these studies.…”
Section: In Vitro Antimicrobial Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Lingonberry polyphenols have also been proposed to act as antivirals [39], and in this regard, lingonberries have been shown to possess in vitro antiviral activity [40]. Other studies have also reported lingonberry's antibacterial and antifungal activities: inhibition of growth of Candida, S. mutans, Porphyromonas gingivalis, Fusobacterium nucleatum, S. aureus, Salmonella enterica sv Typhimurium, S. epidermidis, P. gingivalis, P. intermedia, antiaggregation of S. mutans with Fusobacterium nucleatum or Actinomyces naeslundii, anti-adhesiveness of Neisseria meningitidis or oral streptococci in biofilm formation, and binding activity of Streptococcus pneumoniae, Streptococcus agalactiae and Streptococcus suis to berries and juices [36,[41][42][43][44][45][46][47][48][49][50][51][52]. No effects of lingonberries on lactobacilli have been found in any of these studies.…”
Section: In Vitro Antimicrobial Studiesmentioning
confidence: 96%
“…The randomly chosen adult patients used 10 mL of the juice as a mouthwash twice daily for ten days, after which the trial had to be discontinued because of an unexpected Candida count increases in vivo due to the high sugar content of the juice. In the next clinical studies, the sugar content of the juice was reduced, and lingonberries were shown to have in vivo antimicrobial and anti-inflammatory properties in the form of fermented lingonberry juice (FLJ; Lingora ® , Vantaa, Finland) in clinical human oral studies [44,71] on a total of 40 adults. Initially, FLJ was lyophilized and compressed into tablets [71].…”
Section: In Vivo Human Studiesmentioning
confidence: 99%
“…A clinical study with 30 adult participants tested fermented lingonberry juice antibacterial activity against the oral cavity pathogens Streptococcus mutans and Candida. Compared to the start point, after two weeks of lingonberry mouthwash twice daily, the Streptococcus mutans and Candida counts, visible plaque index (VPI), and bleeding on probing (BOP) were reduced [ 53 ]. Thus, lingonberries can offer a promising natural food derivative to prevent dental caries [ 52 , 53 ].…”
Section: Biological Activity and Health-promoting Effectsmentioning
confidence: 99%
“…Compared to the start point, after two weeks of lingonberry mouthwash twice daily, the Streptococcus mutans and Candida counts, visible plaque index (VPI), and bleeding on probing (BOP) were reduced [ 53 ]. Thus, lingonberries can offer a promising natural food derivative to prevent dental caries [ 52 , 53 ]. Ethanol, methanol, and aqueous extract from lingonberry fruit showed relatively high antimicrobial activity against Escherichia coli , Micrococcus luteus , Pseudomonas putida , Bifidobacterium spp., and Clostridium spp.…”
Section: Biological Activity and Health-promoting Effectsmentioning
confidence: 99%
“…Lingonberries have also been shown to retain their beneficial in vitro and in vivo antimicrobial (e.g., Candida, S. mutans, periodontopathogens) and anti-inflammatory properties in the form of fermented lingonberry juice in a clinical human study (Pärnänen et al, 2019). This study evaluates natural-based polyphenols, especially derived from lingonberries, as plausible antiviral, and antiinflammatory agents and this effect could be monitored with an oral rinse point-of-care test.…”
mentioning
confidence: 99%